Comparative Antibacterial Effects of Honey Bee Propolis on Gram Negative Bacteria Escherichia coli and Gram Positive Bacteria Staphylococcus aureus - Hestiyani, Rani Afifah Nur; Handini, Tri Okmawati; Nitihapsari, Galuh Yulieta; Ning Widhi, Anriani Puspita Karunia; Wahyudin, Wahyudin (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Antimicrobial resistance in pathogens such as Escherichia coli and Staphylococcus aureus poses an urgent global health challenge. Honeybee propolis is known for its promising antibacterial potential.This study aimed to compare the antibacterial effectiveness of propolis against E. coli (Gram-negative) and S. aureus (Gram-positive) using the in vitro disk diffusion method. Propolis was tested at concentrations of 6.25%, 12.5%, 25%, 50%, and 100% against both bacterial species. Disk diffusion assays were conducted on Mueller Hinton Agar, and inhibition zones were measured using a vernier caliper. Data were analyzed using one-way ANOVA. The results showed the Inhibition zone diameters increased with higher propolis concentrations. At 100% concentration, S. aureus showed a 15 mm inhibition zone, while E. coli showed only 7 mm. One-way ANOVA indicated significant differences (p < 0.05) in both bacteria. These findings indicate that propolis exhibits antibacterial activity against both S. aureus and E. coli, with greater effectiveness against Gram-positive S. aureus. These findings support the potential use of propolis as a natural antibacterial agent, particularly for Gram-positive infections.